Analysis of metabolic activity of lactic acid bacteria and yeast in model kefirs made from goat’s milk and mixtures of goat’s milk with mare’s milk based on changes in electrical conductivity and impedance - Dorota Cais-Sokolińska; Jacek Wójtowski; Jan Pikul; Małgorzata Lasik-Kurdyś (Mljekarstvo)
The aim of this study was to analyse the metabolic activity of lactic acid bacteria and yeast based of changes in electrical conductivity and electrical impedance during fermentation of goat milk and mixtures of goat’s milk and mare’s milk (1:1, 1:2). As a result of fermentation, conductivity increased 1.4-fold. The conductivity of kefir prepared from goat and mare milk mixed at a ratio of 1:2 (6.210 Ω-3∙cm-1) was lower than that of the 1:1 mixture or of goat milk alone (7.242 Ω-3∙cm-1). A significant dependence of electrical conductivity and pH (0.970 ≤ r ≤ 0.993) was recorded during fermentation. The addition of mare milk to goat milk significantly slowed down the growth of LAB (Δλ = 0.8 h) and yeasts during kefir production.